Penggunaan Media Internet Sebagai Sumber Belajar di Kalangan Peserta Didik Kelas XII IPS di SMA Pertiwi 1 Padang Pada Masa Pandemi Covid-19 - Siti Annisa Reza; Desri Nora (Universitas Negeri Padang, 2022)
This research was motivated by the use of internet media as a learning resource among students of class XII IPS at SMA Pertiwi 1 Padang during the Covid-19 pandemic. This study aims to explain the use of internet media as a learning resource among students of class XII IPS at SMA Pertiwi 1 Padang. This study uses an approach approach, with the type of phenomenological research, the selection of informants is done by purposive sampling with 18 informants, data collection by observation, in-depth interviews, and documentation studies. Data Reduction (Data Reduction), Data Display (Data Presentation), and Conclusion Drawing/Verification (Conclusion Drawing). The research location is in SMA Pertiwi1 Padang. The results of this study show that there are six motives that cause students to use the internet as a learning resource in the midst of the Covid-19 pandemic. 1) Efforts to fulfill school assignments. 2) Fast pace in information retrieval. 3) Information on learning resources on the internet is more complete. 4) Up-to-date notifications. 5) Make the task easier. 6) Cheaper rates.